O metadiscurso e a construção do ator em Confissões de Ralfo. Uma autobiografia imaginária - Becker, Ruth Maria de Freitas (2008)
Founded on French Semiotics, this study undertakes a reading of Confissões de Ralfo. An imaginary autobiography by Sérgio Sant’Anna. It is a literary work that represents the post modernism and, in this aspect, it keeps away from traditional romanesque models because of its fragmentary structure. Furthermore, it presents a prologue, an epilogue and a final note by the author. It consists of nine little books divided into thirty-two relatively independent units. Considering the complexity of the work, we selected seven out of the thirty-two stories to analyze. The reflection of the enunciator about the act of writing a work and about the construction of the protagonist actor is a characteristic that is revealed throughout the work. To verify how the metadiscourse occurs and the construction of the actor constituted the conducting wire of our analysis always founded on Greimasian semiotics theory. The narrator, the imaginary of the subject of enunciation, assuming dissatisfaction with his personal history, decides to become a character to create his autobiography through the experience of living an imaginary fate. Like this, Ralfo emerges, born from the “death” of the subject of enunciation. Ralfo is constituted as an unstable, multifaceted, “knight errant” in search of adventures, assuming, in each story, different actancial and thematic roles. Key words: Semiotics; metadiscourse; actor; enunciation; enunciate.